Why Do Firms Have “Purpose”? The Firm's Role as a Carrier of Identity and Reputation - Henderson, Rebecca; Steen, Eric Van den (American Economic Review, 2015)
This article develops a theory in which a firm's adoption of a prosocial purpose can increase profitability by strengthening employees' reputation and identity—leading to higher effort and lower wages—as long as implementing purpose is costly with respect to direct monetary payoffs. Employees who value prosocial action will select into firms with a social purpose, which then become a visible carrier for these employees' identity and reputation.